PERENCANAAN KAPASITAS PRODUKSI TAHU PADA IKM TAHU JK JAYA MAKMUR: Capacity planning; Production capacity; RCCP, Tofu production - Zaenal Huda, Zufri; Aji , Bahariandi (LPPM Universitas Putera Batam, 2026)
JK Jaya Makmur Tofu Factory is a local tofu producer that still applies a manual cutting process using knives and simple tools. This condition requires high accuracy and potentially causes variations in cutting results due to worker fatigue and differences in working styles, which in turn increase workload and limit production capacity. Based on data from October 2024 to September 2025, the monthly production target of 150,000–157,000 pieces was not achieved, with actual production reaching only 130,000–140,000 pieces per month and an average achievement rate of 88%. This study aims to determine production capacity requirements, compare required capacity with available capacity, and formulate solutions using the Rough Cut Capacity Planning (RCCP) method. The results show that the required production capacity averages 20,049.5 minutes per month and remains relatively stable throughout the planning period. Meanwhile, the available capacity averages only 9,424.8 minutes per month, indicating that production capacity is insufficient. Based on the calculations, there is a shortage of production capacity, which requires the addition of one worker at each workstation and an additional one working hour per day as a solution.